Impact of Pancreatic Gland Volume on Fistula Formation After Pancreatic Tail Resection - Frozanpor, Farshad; Albiin, Nils; Linder, Stefan; Segersvärd, Ralf; Lundell, Lars; Arnelo, Urban (JOP. Journal of the Pancreas, 2010)
Context Resection of the body and tail of the pancreas (distal pancreatectomy) is associated with high postoperative morbidity, most of which is due to leakage from the pancreatic transection surface. Objective The aim of the current study was to analyze factors which may affect the risk of pancreatic fistula formation. Patients All consecutive distal pancreatectomies prospectively registered in our hospital database from 1999 to 2007 were included. Clinically relevant pancreatic fistula grades B and C, defined according to the International Study Group on Pancreatic Fistula (ISGPF) definition were assessed. Main outcome measures The impact of patient, tumor, surgery, and radiology-related factors on the risk of pancreatic fistula formation were assessed by univariate and multivariate analyses. Results A distal pancreatectomy was performed in 51 patients (median age: 59 years; range: 26-76 years), 22 of whom had malignant and 29 benign or premalignant disease. Pancreatic fistulas were diagnosed in 17 (33.3%) of the patients. An additional three patients had a local abscess without apparent but assumed pancreatic leakage. Multivariate analysis showed that pancreatic fistulas occurred more frequently after hand suturing of the transection area versus the use of a stapler (69.2% vs. 21.1%; OR: 40.4, 95% CI: 3.36-486; P=0.004) and a large volume of the pancreatic remnant (greater, or equal to, 34 cm3) increased the subsequent risk of pancreatic fistula (57.1% vs. 20.8%; OR: 6.14, 95% CI: 1.14-39.0; P=0.035). Conclusions Development of pancreatic fistula after distal pancreatectomy remains a challenge. The volume of the remaining pancreas and the technique of closure of the transected pancreas were found to affect this risk, thus allowing future preventive measures to be explored and evaluated in clinical trials. Image: 3D volume rendering image of the pancreas with the remaining pancreas shown in blue.